Vitamin K2 Inhibits Hepatocellular Carcinoma Cell Proliferation by Binding to 17β-Hydroxysteroid Dehydrogenase 4 - Lu, Xin; Ma, Panpan; Kong, Lingyu; Wang, Xi; Wang, Yaqi; Jiang, Lingling (Frontiers in Oncology, 2021)
Our previous studies have proved that 17β-Hydroxysteroid dehydrogenase 4 (HSD17B4) is a novel proliferation-promoting protein. The over-expression of HSD17B4 promotes hepatocellular carcinoma (HCC) cell proliferation. Vitamin K2 (VK2), a fat-soluble vitamin, has the function of promoting coagulation and can inhibit the progression of liver cancer. A previous study demonstrated that VK2 could bind to HSD17B4 in HepG2 cells. However, the mechanism of VK2 in inhibiting HCC cell proliferation is not clear. In this study, we investigate whether VK2 can inhibit the proliferation of HCC cell induced by HSD17B4, as well as the possible mechanism. We detected the effect of VK2 on HSD17B4-induced HCC cell proliferation, and the activation of STAT3, AKT and MEK/ERK signaling pathways. We measured the effect of HSD17B4 on the growth of transplanted tumor and the inhibitory effect of VK2. Our results indicated that VK2 directly binds to HSD17B4, but does not affect the expression of HSD17B4, to inhibit the proliferation of HCC cells by inhibiting the activation of Akt and MEK/ERK signaling pathways, leading to decrease STAT3 activation. VK2 also inhibited the growth of HSD17B4 induced transplanted tumors. These findings provide a theoretical and experimental basis for possible future prevention and treatment of HCC using VK2.